The Determinants of Inflation in India: The Bounds Test Analysis - Alam, MD Qaiser; Alam, MD Shabbir (International Journal of Economics and Financial Issues, 2016)
India is facing a fast rise in the general price level for the last couple of years. This paper seeks to empirically examine the sources of inflation in India both in the long-run and in the short-run by using the cointegration method developed by Pesaran et al. (2000). The empirical findings suggests that in the long-run money supply, depreciation of the rupee and supply bottlenecks puts a pressure on the domestic price level by causing inflation to rise in the country. The analysis reveals that in the long-run domestic factors as monetary growth and supply bottlenecks dominates the external factors for a rise in the domestic prices in the economy. The short-run analysis also reveals that domestic factor money supply and supply bottlenecks dominate the external factor as a measure cause for a persistent rise in the price level in the country. The supply bottlenecks are though a significant factor in the short-run, but its importance in the long-run is relatively small. Keywords: Inflation, Money Supply, Exchange rate, World Price, GDP gap, Bounds test, ECM JEL Classifications: E31, E51, D51, F43